Pengaruh Art Therapy terhadap Self-Esteem Pasien Skizofrenia - Untari, Rita; Nugroho, Maharso Adhi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Schizophrenia is a psychotic reaction that has signs of withdrawal from social life followed by disturbances in thoughts, emotions, and behavior. Withdrawal from social life will affect the low self-esteem of schizophrenia patients. Low self-esteem causes schizophrenia patients to have difficulty expressing themselves to the environment and people around them. Art therapy is one solution to help reduce negative attitudes towards oneself, explore feelings, manage behavior, and increase self-esteem. Objectives: This study aims to determine whether there is an effect of art therapy on the self-esteem of schizophrenia patients. Methods: This study uses a quantitative pre-experimental approach with the one-group pre and post-test design method. The research sample was schizophrenia patients with disorders in self-esteem at the Dr. Arif Zainudin Surakarta Mental Hospital. Sampling using purposive sampling with a total of 20 samples. The data collection tool was the RSES (Rosenberg Self-Esteem Scale) questionnaire. Hypothesis testing analysis used a paired t-test. Results: The research sample was dominated by male gender (75%), aged 26-35 years (40%), and had the most recent education history at junior high school level (45%). Hypothesis testing showed a p-value of 0.000 (<0.05) which means there is a significant difference in self-esteem before and after doing art therapy activities. Conclusion: Art Therapy activities have an effect on self-esteem in schizophrenia patients at RSJD Dr. Arif Zainudin Surakarta. Keywords: Art Therapy, Self-esteem, Schizophrenia